An alternative electron-donor and highly thermo-assisted strategy for solar-driven water splitting redox chemistry towards efficient hydrogen production plus effective wastewater treatment. (October 2021) - Jiang, Hong; Wang, Xirui; Li, Chaoying; Gu, Di; Jiang, Tingting; Nie, Chunhong; Yuan, Dandan; Wu, Hongjun; Wang, Baohui
Abstract: An alternative technology has been sought for highly efficient and sustainable hydrogen production and wastewater treatment worldwide. This paper is focused on the intersection of solar energy, wastewater treatment and hydrogen production. The solar thermo-assisted and electron-donor alternative strategy was conducted for water-splitting redox chemistry to target highly efficient hydrogen production and effective wastewater treatment. The thermodynamic calculation displays that the solar thermal application and shuttle sulfide electron donor alternative are favorable for the hydrogen production and sulfide-to-sulfate oxidation by the falling trend in the potential (from 1.5V to 0.6V). The curves revealed that high current peaks in the low potential range were dominated by the thermal-assisted process and the alternative of the oxidation half-reaction. The experiments illustrated that solar thermal utilization and sulfide donors were dominant factors for the high efficiencies. Under the outdoor sunlight, the high hydrogen production rate and sulfide conversion efficiency were experimentally achieved at rates of 0.25 mL/h H2 and 93% sulfide-to-sulfate oxidation, reasonably more than that of the direct electrochemical water splitting to hydrogen (nearly no evolution) under the same applied bias (＜1.2V). The system realized that one sustainable technology conducts simultaneously both highly efficient hydrogen production and highly effective water treatment. Highlights: An efficient strategy was proposed and constructed for solar-enabled hydrogen and water treatment. A solar system was greatly enhanced by solar heat and wastewater shuttle-electron donors. The realization was achieved for highly efficient hydrogen and effective water treatment. The response was contributed by the alternative half-reaction and the complete oxidation of sulfide to sulfate.